Aggregatibacter actinomycetemcomitans serotypes, the JP2 clone and cytolethal distending toxin genes in a Thai population - Bandhaya P. (2014)
Aim To examine the genetic diversity of Aggregatibacter actinomycetemcomitans in Thai adults. Materials and Methods Subgingival plaque samples from 453 subjects were analysed for A. actinomycetemcomitans serotypes, the presence of the high leukotoxin-producing JP2 clone and cytolethal distending toxin genes (cdtABC) using the polymerase chain reaction technique. In subjects who were positive for cdtABC, restriction fragment length polymorphism analysis was used to identify a single nucleotide polymorphism (SNP) in the cdtB gene at amino acid position 281. The extent and severity of periodontal disease were compared between subjects harbouring different A. actinomycetemcomitans genotypes. Results Eighty six subjects (19%) were positive for A. actinomycetemcomitans. The JP2 clone was not detected. Serotype c was the most prevalent (57%), followed by serotypes a (33%) and b (7%). Among A. actinomycetemcomitans-positive subjects, 27% were positive for cdtABC. All cdtABC-positive subjects possessed the SNP in the cdtB, which is involved with increased toxin activity. The presence of A. actinomycetemcomitans, but not a specific genotype, was significantly related to increased probing depth and periodontal attachment loss. Conclusions Our results confirm the previous findings that genotype distribution of A. actinomycetemcomitans varies between ethnic groups. However, no clear relationship between a specific genotype and periodontal conditions was observed. © 2012 John Wiley & Sons A/S.